Analisis Efisiensi Bank Umum Konvensional di Indonesia - Yewisa, Tania Dara; Satrianto, Alpon (Jurnal Informatika Ekonomi Bisnis, 2025)
This study aims to analyze the efficiency level of conventional commercial banks in Indonesia based on asset classification during the 2019–2023 period. The method used is Data Envelopment Analysis (DEA) with a Constant Returns to Scale (CRS) approach. The sample consists of 29 banks, divided into two groups: 20 large-asset banks and 9 medium-asset banks. The input variables include fixed assets, equity, and operating expenses, while the output is net profit. The results show that large banks had a higher average efficiency than medium-sized banks. In 2023, the average efficiency score for large banks reached 0.7012, while medium-sized banks scored only 0.2917. The minimum efficiency scores for large and medium banks were 0.0475 and 0.0352, respectively. The percentage of large banks achieving optimal efficiency (DEA=1) ranged from 5% to 35%, while for medium banks it ranged from 5% to 22.2%. BCA and OCBC NISP consistently achieved efficiency and served as benchmarks for other banks. Differences in efficiency are influenced by business scale, technology adoption, and cost management. These findings provide a vital foundation for improving operational strategies and bank efficiency in Indonesia.